2017
DOI: 10.1101/154450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corrigendum and follow-up: Whole genome sequencing of multiple CRISPR-edited mouse lines suggests no excess mutations

Abstract: Our previous publication suggested CRISPR-Cas9 editing at the zygotic stage might unexpectedly introduce a multitude of subtle but unintended mutations, an interpretation that not surprisingly raised numerous questions. The key issue is that since parental lines were not available, might the reported variants have been inherited? To expand upon the limited available whole genome data on whether CRISPR-edited mice show more genetic variation, whole-genome sequencing was performed on two other mouse lines that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A WGS approach to off-target mutation detection was also used by Schaefer et al (16) to identify off-target mutations in two gene-edited mice generated by single-cell embryo injection (17). Schaefer et al (16) reported hundreds of off-target mutations by WGS comparison to a single untreated mouse, but this result was found to be flawed when the authors later reported no excess mutations upon conducting WGS analysis with additional mouse lines (18). These studies highlight the importance of considering inherited and spontaneous mutations when investigating off-target events, and the use of appropriate controls that enable these considerations to be made.…”
Section: Introductionmentioning
confidence: 99%
“…A WGS approach to off-target mutation detection was also used by Schaefer et al (16) to identify off-target mutations in two gene-edited mice generated by single-cell embryo injection (17). Schaefer et al (16) reported hundreds of off-target mutations by WGS comparison to a single untreated mouse, but this result was found to be flawed when the authors later reported no excess mutations upon conducting WGS analysis with additional mouse lines (18). These studies highlight the importance of considering inherited and spontaneous mutations when investigating off-target events, and the use of appropriate controls that enable these considerations to be made.…”
Section: Introductionmentioning
confidence: 99%
“…This specific issue remains, however, highly controversial. In March 2018, Schaefer and colleagues retracted their paper-in the face of pressure from some members of the scientific community working on crispr-on the grounds that the study results were irreproducible and unsupported by the data, and the study lacked key controls (Editorial, 2018;Schaefer et al, 2018). Retraction of this paper does not, of course, remotely prove or even suggest that crispr is sufficiently free of off-target effects to be safely used in humans.…”
mentioning
confidence: 99%
“…Retraction of this paper does not, of course, remotely prove or even suggest that crispr is sufficiently free of off-target effects to be safely used in humans. Most stakeholders who have opined in its wake have urged further progressive, yet cautious, research to elucidate the situation and stopped short of inferring an all clear from the authors' most recent work (Schaefer et al, 2018). With particular regard to their revision, Schaefer et al are careful to note (correctly) that their latest data suggest that, "in specific cases, crispr […] may not introduce numerous, off-target mutations" (Abstract).…”
mentioning
confidence: 99%